Primary cytoreductive surgery followed by chemotherapy compared to neoadjuvant chemotherapy followed by cytoreduction as a treatment for stage III and IV ovarian cancer (literature review) - E. V. Sibirskaya; P. O. Nikiforova; N. R. Rabadanova (Опухоли женской репродуктивной системы)
Standard treatment for advanced ovarian cancer (OC) consists of a combination of chemotherapy and cytoreductive surgery, but practice varies depending on the order of these 2 procedures: neoadjuvant chemotherapy followed by interval debulking surgery or primary cytoreduction followed by adjuvant chemotherapy. The aim of the work is to evaluate methods of treatment of OC of stages III, IV according to FIGO.The literature review includes publications in English from the PubMed, CochraneLibrary and Google Scholar databases on the use of neoadjuvant therapy and primary cytoreduction in late stages of OC (FIGO III–IV). 6 randomized controlled trials, 8 meta-analyses, 8 systematic reviews, 1 case report were identified. Data from publications were distributed according to the criteria for assessing the effectiveness of the treatment: overall and relapse-free survival, perioperative complications, quality of life of patients and the grade of cytoreduction.Neoadjuvant chemotherapy + interval debulking surgery is not inferior to primary debulking surgery + adjuvant chemotherapy in terms of survival outcomes in selected patients, but treatment with neoadjuvant chemotherapy + interval debulking surgery improves perioperative outcomes and optimal cytoreduction rates. It is needed to focus on finding optimal criteria for selecting patients in both groups in future studies of this issue. It is necessary to take into account X-ray, histological studies, the molecular subtype of the tumor, the patient’s condition, the qualifications of the surgical team, the drugs included in chemotherapy.